Polypill eligibility and equivalent intake in a Swiss population-based study - Julien Castioni (Nature Portfolio, 2021)
Abstract The polypill has been advocated for cardiovascular disease (CVD) management. The fraction of the population who could benefit from the polypill in Switzerland is unknown. Assess (1) the prevalence of subjects (a) eligible for the polypill and (b) already taking a polypill equivalent; and (2) the determinants of polypill intake in the first (2009–2012) and second follow-ups (2014–2017) of a population-based prospective study conducted in Lausanne, Switzerland. The first and the second follow-ups included 5038 and 4596 participants aged 40–80 years, respectively. Polypill eligibility was defined as having a high CVD risk as assessed by an absolute CVD risk ≥ 5% with the SCORE equation for Switzerland and/or presenting with CVD. Four polypill equivalents were defined: statin + any antihypertensive with (A) or without (B) aspirin; statin + calcium channel blocker (CCB) (C); and statin + CCB + angiotensin-converting enzyme inhibitor (D). The prevalence of polypill eligibility was 20.6% (95% CI 19.5–21.8) and 27.7% (26.5–29.1) in the first and second follow-up, respectively. However, only around one-third of the eligible 29.5% (95% CI 26.7–32.3) and 30.4% (27.9–33.0) respectively, already took the polypill equivalents. All polypill equivalents were more prevalent among men, elderly and in presence of CVD. After multivariable adjustment, in both periods, male gender was associated with taking polypill equivalent A (OR: 1.93; 95% CI 1.45–2.55 and OR: 1.67; 95% CI 1.27–2.19, respectively) and polypill equivalent B (OR: 1.52; 95% CI 1.17–1.96 and OR: 1.41; 95% CI 1.07–1.85, respectively). Similarly, in both periods, age over 70 years, compared to middle-age, was associated with taking polypill equivalent A (OR: 11.71; CI 6.74–20.33 and OR: 9.56; CI 4.13–22.13, respectively) and equivalent B (OR: 13.22; CI 7.27–24.07 and OR: 20.63; CI 6.51–56.36, respectively). Former or current smoking was also associated with a higher likelihood of taking polypill equivalent A in both periods. A large fraction of the population is eligible for the polypill, but only one-third of them actually benefits from an equivalent, and this proportion did not change over time.